Development of Philosophy Based-Students Worksheet on the Matrix - Somakim; Zahwa, Nur; Nuraeni, Zuli; Araiku, Jeri (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
This study focused on developing student worksheet (SW) based on philosophy on the topic of matrix operations, including an overview of its effect on students' conceptual understanding abilities of grade XI at Senior High School (SMA in Bahasa) IT Bina Ilmi Palembang. It discussed how the student worksheet produced could be valid, practical, and had potential effects. The method used was development research consisting of preliminary, prototyping and assessment phase stages. This student worksheet consisted of the history of the matrix (ontology), matrix operation procedures (epistemology) and implementation of the matrix (axiology). The results showed that the validity of the student worksheet amounted to 84.1% with a valid category and could be used with minor revisions. The practicality score at the small group stage was 87.8% with a very practical category. Statistical results showed that there was an increase in the average score of a significant test result of 59.06. This showed that there was a positive effect from the use of philosophy-based SW on students' conceptual understanding. Based on these results, the philosophy-based student worksheet developed was categorized as valid, practical, and effective in improving students' conceptual understanding ability on matrix material. DOI: https://doi.org/10.22342/jpm.17.2.19782.149-166